Innocube box / Aiman Iman Shaifuddin … [et al.]. - Shaifuddin, Aiman Iman; Alias, Juliani; Fairuz, Fida Naziha; Suhaimi, Nur Amyshazlianna; Hardy Azmir, Batrisyia Syahirah; Samsudin, Siti Nurizzati Atirah (2024)
Brief description of the business and product concepts: Maverick launched a firm that aims to meet the changing patterns in how consumers watch films and watch web series. The business has noticed a frequent issue as smartphone content viewing grows in popularity: sacrificing clarity and sharpness when utilizing a smartphone as the primary viewing device. Maverick has created a new product concept called Innocube, which is essentially a phone magnifier that makes use of convex lens technology, in order to address this problem. The purpose of the Innocube is to enlarge the screen of smartphones, giving users a better and more visible viewing experience. This invention makes use of the idea of a convex lens, which is comparable to a regular magnifying glass, to increase the size of the images on the screen. The gadget is intended to provide an affordable option for consumers who might find computers and TVs to be rather expensive or cumbersome. The company intends to improve the content consuming experience on smartphones by utilizing technology that magnifies images. It acknowledges that smartphones are widely used for this purpose. The target market and projections: The device Innocube, which is intended for smartphone screen magnification, is aimed at a demographic that is mainly composed of people between the ages of 15 and 24, with a particular emphasis on adults and students (80%) and teenagers (20%). According to the report, there is more appeal to women (71.4%) and general customer acceptance (91.4%). Respondents place a high value on usefulness, with 62.9% wishing for items such as a table, fan, and large screen. Affordability (8.6%) and portability (22.9%) are also important factors. 60% of the market believes that a price range of RM20 to RM25 is appropriate, indicating that they are willing to invest in the product. According to projections, Innocube is positioned for possible success in the targeted market categories by emphasizing price, portability, and functionality—all of which are in line with customer desires.